Self-resonant modes in Josephson junctions with a phase discontinuity - Nappi, C.; Adamo, M.; Sarnelli, E.; Goldobin, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We extend the theory of self-resonances in short Josephson junctions to the case of a piecewise constant critical current density and a κ discontinuity of the Josephson phase. We calculate the amplitudes of self-resonances as a function of applied magnetic field by using an extension of the approach introduced by Kulik for conventional Josephson junctions (I.O. Kulik, JETP Lett. 2, 84 (1965)). The presented theory agrees with existing experiments on superconducting–insulator–ferromagnet–superconductor 0–π Josephson junctions. The results are relevantfor the characterization of all modern 0–π junctions as well as 0–κ junctions with artificially created phase discontinuity: high-temperature grain boundary junctions, junctions with ferromagnetic barrier and the junction with current injectors.